A cross-sectional study on the application of patient-reported outcome measurements in clinical trials of traditional Chinese medicine in mainland China - Dong, Yue; Liu, Lin; Zhang, Xiaowen; Gong, Yijia; Yan, Shiyan; Li, Wei; Li, Shunping; Rong, Hongguo; Liu, Jianping (Frontiers in Pharmacology, 2023)
Objectives: Patient-reported outcomes (PROs) provide a global perspective of patient health status which plays an enormous role in evaluating clinical efficacy. However, the application of PROs in traditional Chinese medicine (TCM) was still insufficiently studied in mainland China. Methods: This cross-sectional study was performed based on interventional clinical trials of TCM that were conducted in mainland China from January 1, 2010, to July 15, 2022. We included interventional clinical trials of TCM for which the country of the primary sponsors or recruitment settings in mainland China. Data was retrieved from the ClinicalTrials.gov and Chinese Clinical Trial Registry. For each included trial, data including clinical trial phases, study settings, participant’s age, sex, diseases, and the patient-reported outcome measures (PROMs) were extracted. Trials were categorized into four categories according to (1) listed PROs as primary endpoints, (2) listed PROs as secondary endpoints, (3) listed PROs as coprimary outcomes (both primary and secondary endpoints), and (4) did not mention any PROMs. Results: Among a total of 3797 trials, 680 (17.9%) trials listed PROs as primary endpoints, 692 (18.2%) trials listed PROs as secondary endpoints, and 760 (20.0%) trials listed PROs as coprimary endpoints. Among 675 787 participants included in the registered trials, 448 359 (66.3%) patients’ data were scientifically collected by PRO instruments. Neurological diseases (11.8%), musculoskeletal symptoms (11.5%), mental health conditions (9.1%) were the most common conditions evaluated by PROMs. Disease-specific symptoms related concepts were used most frequently (51.3%), followed by health-related quality of life concepts. Visual analog scale, 36-item Short-Form Health Questionnaire, and TCM symptom score were the most common PROMs in these trials. Conclusions: In this cross-sectional study, the use of PROs increased in the past decades according to clinical trials of TCM conducted in mainland China. Considering that the application of PROs in clinical trials of TCM has some existing issues including uneven distribution and lack of normalized PROs of TCM, further study should be focused on the standardization and normalization of TCM-specific scales.